James Joyce, Ulysses, and the construction of Jewish identity : culture, biography, and "the Jew" in modernist Europe - Davison, Neil R. (New York : Cambridge University Press, 1996)
Representations of 'the Jew' have long been a topic of interest in Joyce studies. Neil Davison argues that Joyce's lifelong encounter with pseudo-scientific, religious and political discourse about 'the Jew' forms a unifying component of his career. Davison offers new biographical material, and presents a detailed reading of Ulysses showing how Joyce draws on Christian folklore, Dreyfus Affair propaganda, Sinn Fein politics, and theories of Jewish sexual perversion and financial conspiracy. Throughout, Joyce confronts the controversy of 'race', the psychology of internalised stereotype, and the contradictions of fin-de-siècle anti-Semitism.
Foreword: Anthony Julius -- Introduction -- Silence: family values -- Silence: Jesuit years: Clongowes and Belvedere -- Silence: university years: the Church, Dreyfus, and aesthetics -- Exile: excursion to the Continent, bitter return -- Cunning and exile: Greeks and Jews -- Cunning: Jews and the Continent: texts and subtexts -- Cunning: the miracle of Lazarus times two: Joyce and Italo Svevo -- Ulysses -- Conclusion -- Notes -- Bibliography -- Index.
Includes bibliographical references (pages 285-297) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Joyce, James, -- 1882-1941.; Joyce, James, -- 1882-1941 -- Religion; Joyce, James, -- 1882-1941 -- Characters -- Jews; Joyce, James, -- 1882-1941; Ulysses (Joyce, James); Bloom, Leopold -- (Fictitious character); Jews in literature; Antisemitism -- History -- 20th century; Bloom, Leopold (Fictitious character); Stereotypes (Social psychology) in literature; Novelists, Irish -- 20th century -- Biography; Antisemitism -- History -- 20th century; Juifs dans la littérature.; Antisémitisme -- Histoire -- 20e siècle.; Stéréotypes dans la littérature.; Romanciers irlandais -- 20e siècle -- Biographies; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Antisemitism; Jews in literature; Novelists, Irish; Religion; Stereotypes (Social psychology) in literature; 1900-1999; Biography; Biographies; History; Biographies; Biographies